Pengembangan Media Pembelajaran ‘Kenalin’ Berbasis Aplikasi Smart Apps Creator Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas IV Sekolah Dasar - Na'im Mushlihurrohman; Suratno (Jurnal Penelitian Pendidikan IPA, 2024)
Science and Technology learning in class IV at SD Negeri Kandri 01 is still not optimal in the use of IT-based learning media. This affects the learning outcomes of students who have not met the KKTP. This research aims to develop, and test the feasibility, and effectiveness of the "Kenalin" learning media based on the Smart Apps Creator application for the material Indonesiaku Kaya Budaya and also to find out whether the 'Kenalin' learning media can significantly improve student learning outcomes. This type of research is Research and Development (R&D) with the Borg and Gall development model. Using test techniques (pretest and posttest) and non-test techniques (observation, interviews, initial data analysis, and final data analysis). The data analysis method used in this research includes initial data analysis using the normality test, as well as final data analysis using the average difference test using theT-Test and measuring the average increase using N-Gain. Based on the results of material validation and media validation, it was found that the 'Kenalin' media met the standard criteria for being very worthy with a score of 92.50% from material expert validators and 95% from media expert validators. The effectiveness of using the 'Kenalin' media was assessed by comparing the pretest and posttest scores using the N- Gain test which obtained a score of 0.58 which was included in the medium category and the paired simple test obtained a result of 0.000 <0.005, so Ho was rejected and Ha was accepted. This research concludes that the "Kenalin" learning media based on Smart Apps Creator is suitable and effective for use as a learning media for the material My Indonesia is Rich in Culture, student learning outcomes also show a significant improvement.